Biomonitoring metals in leeches (Hirudinaria manillensis): a step towards its immediate application in traditional medical treatments - Helal Uddin, A.B.M.; Alaama, Mohammed; Abdualkader, Abdualrahman Mohammed; Khalid, Reem S. (2014)

(untitled)
Leech Saliva Extract (LSE) has been known to possess wide range of biological activities such as antithrombin, antidiabitic and anticancer. The natural bioactive peptides and proteins found in LSE are promising active pharmaceutical ingredient to develop new therapeutic pharmaceutical formulations. Those formulations can provide benefits for health and environmental safety by applying green production procedure. The traces of heavy metals were investigated in the tissues and saliva extracts of leeches (Hirudinaria manillensis) collected from Cheneh lake, Terengganu, Malaysia. Concentration of selected heavy metals such as Cadmium (Cd), Chromium (Cr), Iron (Fe), Manganese (Mn), Nickel (Ni), Lead (Pb), Selenium (Se) and Zinc (Zn) were detected using ICP-MS. Almost all heavy metal concentrations in lake water were found to be higher than the Maximum Permissible Limits (MPL) and placed under class III Interim National Water Quality Standards For Malaysia (INWQS). Furthermore, trace amounts of heavy metals were found in leeches’ tissues and LSE. Such concentrations of heavy metals can be a source of health hazard if LSE product was prepared directly from the collected leeches without previous purification procedure. In this study, we described a method to reduce the metal levels in leech saliva by adopting frequent washing procedure using non-chlorinated or distilled water for a period of three successive weeks. The described procedure significantly reduced the concentrations of tested metals (p < 0.05), especially the deduction of Cd level up to 99.7% in leech saliva and 92.38% reduction in leeches’ tissues in case of Pb concentration. We conclude that constant washing procedure would help in safe utilization of LSE in green industrial pharmacy. Key words: leeches, saliva, extract, heavy metals, ICP-MS